INTEGRASI BISNIS INKLUSIF DAN COMMUNITY-BASED TOURISM DI LOMBOK TENGAH - Firdaus, M. Surya Maulana; Widiyanto, Nur; Syamsu, Moch. Nur; Nugroho, Agung Yuliyanto; Suswanto, Suswanto (Smart Education, 2025)
Abstract: Community-Based Tourism/CBT is a tourism approach that places the community as the main actor. In order for economic and social benefits to be more evenly distributed, an implementation model with an inclusive business approach is needed in its management. This study aims to analyze the implementation of inclusive business in the development of CBT in Sukarara and Bilebante Tourism Villages, Central Lombok. The research method used is qualitative descriptive, with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that Sukarara Village has succeeded in implementing the principles of inclusive business through strengthening local weaving businesses, training, access to capital, and partnerships with the tourism sector. In contrast, Bilebante Village still faces obstacles in institutional capacity and market access even though it has the potential for local herbal businesses. The conclusion of this study shows that the implementation of inclusive business can strengthen the development of CBT fairly and sustainably if supported by cross-sector collaboration, increasing community capacity, and policies that favor locality. This study contributes to strengthening the theory of inclusive business in the tourism sector and offers applicable policy recommendations for the development of tourist villages. Keywords: Inclusive Business, Community-Based Tourism, Tourism Village, Community Empowerment Abstrak: Community-Based Tourism/CBT merupakan pendekatan pariwisata yang menempatkan masyarakat sebagai pelaku utama. Agar manfaat ekonomi dan sosial lebih merata, diperlukan model penerapan dengan pendekatan bisnis inklusif dalam pengelolaannya. Penelitian ini bertujuan untuk menganalisis implementasi bisnis inklusif dalam pengembangan CBT di Desa Wisata Sukarara dan Bilebante, Lombok Tengah. Metode penelitian yang digunakan adalah kualitatif deskriptif, dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa Desa Sukarara telah berhasil menerapkan prinsip bisnis inklusif melalui penguatan usaha tenun lokal, pelatihan, akses modal, serta kemitraan dengan sektor pariwisata. Sebaliknya, Desa Bilebante masih menghadapi kendala dalam kapasitas kelembagaan dan akses pasar meskipun memiliki potensi usaha herbal lokal. Kesimpulan dari penelitian ini menunjukkan bahwa implementasi bisnis inklusif dapat memperkuat pengembangan CBT secara adil dan berkelanjutan jika didukung oleh kolaborasi lintas sektor, peningkatan kapasitas masyarakat, dan kebijakan yang berpihak pada lokalitas. Penelitian ini memberikan kontribusi terhadap penguatan teori bisnis inklusif di sektor pariwisata serta menawarkan rekomendasi kebijakan yang aplikatif untuk pengembangan desa wisata. Kata kunci: Bisnis Inklusif, Community-Based Tourism, Desa Wisata, Pemberdayaan Masyarakat